Consciência Vocal e Musical no teatro: uma proposta para o ensino superior - Priscilla Romualdo Cler dos Reis (2013)
This paper deals with the voice of the actor and his training in higher education. At first, addresses the issue of vocal training under a Brazilian perspective by studying articles, theses and dissertations produced by teachers in state and federal universities, published in the last ten years. Then, the work focuses on teaching voice in Undergraduate Theatre course in the School of Fine Arts of the Federal University of Minas Gerais, through the presentation and analysis of the course and subjects in the area of voice currently offered. The last part of this paper proposes a reform of the curriculum of Theatre at UFMG, by creating a compulsory subject (Vocal and Musical Awareness Workshop), detailed in the final chapter of this dissertation. The subject proposal addresses key issues in vocal training of the actor as vocal technique and awareness of soundparameters (height, duration, intensity and timbre).